PEMBUATAN PROGRAM INTERFACE UNTUK PENGONTROLAN RV-M1 - Endra, Endra; H, Silvester; Yonny, Yonny; Titan, Galang (Bina Nusantara University, 2007)
Article explores the making of interface of RV-M1 hand robot control that replaced the cosiprog program,a program that is able to help student in Mecatronica-1 Practice, and able to control the hand robot by localnetwork by two user or more. The used methods were literature study, and field study, that is design method. Theresearch result are control of hand robot on X,Y,Z axis and point to point, the use of local network to control thehand robot, save certain position, and use several user to control the robot.Keywords: interface program, robot, local network